An epigenetic hypothesis for the genomic memory of pain - Alvarado, Sebastian; Tajerian, Maral; Suderman, Matthew; Machnes, Ziv; Pierfelice, Stephanie; Millecamps, Magali; Stone, Laura S.; Szyf, Moshe (Frontiers in Cellular Neuroscience, 2015)
Chronic pain is accompanied with long-term sensory, affective and cognitive disturbances. What are the mechanisms that mediate the long-term consequences of painful experiences and embed them in the genome? We hypothesize that alterations in DNA methylation, an enzymatic covalent modification of cytosine bases in DNA, serve as a “genomic” memory of pain in the adult cortex. DNA methylation is an epigenetic mechanism for long-term regulation of gene expression. Neuronal plasticity at the neuroanatomical, functional, morphological, physiological and molecular levels has been demonstrated throughout the neuroaxis in response to persistent pain, including in the adult prefrontal cortex (PFC). We have previously reported widespread changes in gene expression and DNA methylation in the PFC many months following peripheral nerve injury. In support of this hypothesis, we show here that up-regulation of a gene involved with synaptic function, Synaptotagmin II (syt2), in the PFC in a chronic pain model is associated with long-term changes in DNA methylation. The challenges of understanding the contributions of epigenetic mechanisms such as DNA methylation within the PFC to pain chronicity and their therapeutic implications are discussed.